ORNANOLEPTIC TEST AND NUTRITIONAL CONTENT OF CHIPS WITH THE ADDITION OF GREEN SPINACH FLOUR IN DENAI KUALA VILLAGE, PANTAI LABU DISTRICT - Futri Ritonga; Rani Suraya (Journal of Gender and Social Inclusion in Muslim Societies, 2025)
Anemia is a common health problem among adolescent girls in Indonesia, primarily due to iron deficiency. Anemia prevention efforts can be achieved by increasing the consumption of iron-rich regional foods, such as green spinach. This study aimed to determine the organoleptic properties (color, aroma, taste, and texture) and nutritional content, particularly iron content, of chips with the addition of green spinach flour. The study was conducted in Denai Kuala Village, Pantai Labu District. This study used an experimental method with a Completely Randomized Design (CRD) design. There was one control group and three treatments, each with the addition of green spinach flour (F0 = 0 g, F1 = 20 g, F2 = 40 g, and F3 = 60 g), with three replications. The results were analyzed using ANOVA. If a significant effect was found, the results were followed by Duncan's Multiple Range Test (DRR). Organoleptic testing was conducted on 30 panelists of adolescent girls aged 14-20 years. The results showed that F1 was the most preferred sample by the panelists, with average scores for color (4.03), aroma (4.13), taste (3.43), and texture (3.47). Meanwhile, F3 had the highest iron content (100.2 mg/kg).